TAFSIR AYAT-AYAT PERENCANAAN PERSPEKTIF AL-QURAN DAN AL-HADIST - Dinda Luthfiaturrahman Alhaq; Hamidullah Mahmud (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The importance of planning in life, especially since many people do not understand it and tend to act hastily. Planning is the first step to achieving goals through the determination of the necessary steps. The purpose of this research is to analyse the verses of planning from the perspective of Al-Quran and al-Hadist. This research is included in the type of qualitative research , more precisely descriptive qualitative with library research data sources or literature, whose findings are not achieved by statistical procedures. The results of this study indicate that Q.S Al-Hasyr Verse 18: This verse calls Muslims to piety and self-reflection in preparation for the hereafter. Piety to Allah is the core of faith, and every action will be accounted for. Q.S Fathir Verse 11: This verse emphasises that the creation of man and all events, including life and death, are within the knowledge and decree of Allah. Q.S Al-Anfal Verse 60: This verse calls for thorough preparation in the face of the enemy, covering various aspects of life, not just military. Planning in the Perspective of Al-Hadith, Rasulullah SAW emphasised the importance of planning in every activity. Hadith teaches that every deed should be planned with clear intentions. He said about time: ‘Be thou in this world as a traveller...’ reminds us to make good use of time. The word about intention: ‘A deed is accompanied by its intention...’ emphasises the importance of intention in every action.